Pyoderma gangrenosum in ulcerative colitis patient treated with vedolizumab: adsorptive granulocyte/monocyte apheresis as a new therapeutic option refractory cases - a case report and literature review - Mauro Mastronardi; Elisabetta Cavalcanti; Nunzia Labarile; Raffaele Armentano; Francesco Gabriele; Margherita Curlo (SAGE Publishing, 2023)
Extraintestinal manifestations occur rather frequently in ulcerative colitis (UC) and Crohn's disease patients and are usually related to an exacerbation of the underlying intestinal bowel disease but sometimes may run a course independent of the inflammatory bowel diseases (IBD). About one-third of patients with IBD develop extraintestinal manifestations, such as pyoderma gangrenosum (PG). PG is an uncommon inflammatory skin disorder of unknown pathogenesis. There are no specific serological or histological markers, and diagnosis is predominantly clinical. Topical and systemic therapies are both vital aspects of treatment and immune modulators have been used with increasing success in recent years, although immunosuppressive drugs raise some concerns due to an increased risk of serious and opportunistic infections and cancer, particularly in elderly and comorbid patients, underlining the unmet need for safer alternative therapies. Thus, in this case report, we highlighted an adsorptive granulocyte/monocyte apheresis (GMA) as a new therapeutic possibility in IBD patients with extraintestinal manifestations. We report a case of a 60-year woman with a history of UC with a Mayo grade 3 score which was associated with a PG. Given that the patients maintained clinical remission with vedolizumab, we preferred not to perform a combined treatment with other antitumor necrosis factor-alpha or ciclosporin, thus avoiding an increased risk of serious infections in the patient. Therefore, we performed the extracorporeal leukocyte apheresis. The patient progressed favorably, with progressive improvement of skin and bowel disease. Therefore, adsorptive GMA has a very favorable safety profile and has been confirmed in numerous studies. In this study, we underlined that an intensive regimen of GMA paves the way to an ideal option for patients with severe and refractory PG complicated with UC.